Negotiating change: community mental health and addiction practice in the Northwest Territories of Canada - Kronstal, Alana (2009)
The purpose of this study was to explore the experiences and support needs of community mental health and addiction services providers in the context of rapid social and economic change in communities in the Northwest Territories (NWT) of Canada. Two main questions guiding this inquiry were: How do community mental health and addictions workers experience and respond to rapid socio-economic change in relation to their professional practice? What are the support needs of practitioners in light of continued change in the region? Primary data consisted of personal interviews with 15 community-based mental health and addictions practitioners throughout the NWT. Findings drawn from the thematic analysis of these interviews highlight the positive and negative changes taking place in communities with respect to mental health and addictions, the significant impact of organizational change on front-line practice, and the possibilities that exist for the future of mental health and addiction service delivery in the NWT. In the discussion chapter, community-based practitioners’ views are related to key themes within the literature and recommendations to improve the NWT mental health and addiction services policies and practices are made.